Absolute SILAC-Compatible Expression Strain Allows Sumo-2 Copy Number Determination in Clinical Samples - Matic, Ivan (American Chemical Society, 2011)
[Image: see text] Quantitative mass spectrometry-based proteomics is a vital tool in modern life science research. In contrast to the popularity of approaches for relative protein quantitation, the widespread use of absolute quantitation has been hampered by inefficient and expensive production of labeled protein standards. To optimize production of isotopically labeled standards, we genetically modified a commonly employed protein expression Escherichia coli strain, BL21 (DE3), to construct an auxotroph for arginine and lysine. This bacterial strain allows low-cost, high-level expression of fully labeled proteins with no conversion of labeled arginine to proline. In combination with a fluorescence-based quantitation of standards and nontargeted LC–MS/MS analysis of unfractionated total cell lysates, this strain was used to determine the copy number of a post-translational modifier, small ubiquitin-like modifier (SUMO-2), in HeLa, human sperm, and chronic lymphocytic leukemia cells. By streamlining and improving the generation of labeled standards, this production system increases the breadth of absolute quantitation by mass spectrometry and will facilitate a far wider uptake of this important technique than previously possible.